Initiating Discourse on Toraja Church Economic Theology: Role of Tongkonan in Forming and Developing Economic Theology in Toraja Church - Oktavianus Pasoloran; Rannu Sanderan; Alpius Pasulu (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat)
This research intends to initiate and formulate the economic theology of the Toraja Church based on a biblical view, and it is realized that it requires challenging and complex efforts. The field of Economics is vast and significant, and therefore, in the context of the Toraja Church, theology is inclined to aid economists in establishing an ethical, faith-based groundwork for the development of economics. The extensive scope of this inquiry has motivated the Toraja Church to initiate this investigation as a foundation for fostering sustainable research pertinent to the economic realm of Torajan population. This research carries out using a qualitative method. Primary data were collected by means of observations and interviews during various mini-tours and live-ins of field research. Both personal interviews and those in the form of tentative-by-the-run FGD were conducted. To support them, referential data were collected by literature review and documentation from various stakeholders. This study recognizes 1) God's mandate to organize the economy, 2) preferential options for the poor, and 3) economic empowerment as a responsible duty. However, in its fundamentals the Toraja Church should build its economic theology based on Biblical principles, taking consideration of its experience & history and the community’s socio-cultural context.